2009
DOI: 10.1002/jcp.21791
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear cyclin D1: An oncogenic driver in human cancer

Abstract: Perturbations in the regulation of the core cell cycle machinery are frequently observed in human cancers. Cyclin D1 which functions as a mitogenic sensor and allosteric activator of CDK4/6, is one of the more frequently altered cell cycle regulators in cancers. Cyclin D1 is frequently overexpressed in cancers and its overexpression can be attributed to many factors including increased transcription, translation, and protein stability. Although cyclin D1 overexpression is clearly implicated in the affected can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
339
1
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(361 citation statements)
references
References 56 publications
11
339
1
10
Order By: Relevance
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumors exhibit abnormalities within the RB-p16-cyclin D1 pathways, and often these lead to increased activity of cyclin D1. [10][11][12] However, we have noted in routine practice that adenocarcinoma in situ and invasive cervical adenocarcinoma usually lack expression of cyclin D1, whereas the nuclei of most normal endocervical epithelial cells are positively stained. This seems a surprising finding as neoplastic endocervical lesions are typically characterized by prominent mitotic activity and show increased expression of the proliferationassociated marker Ki-67/MIB-1.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…p53 is a tumor suppressor gene that promotes apoptosis but also inhibits cell proliferation (11). Cyclin D 1 regulates cyclin-dependent kinases (CDKs), which increase cell proliferation (12). Neither cigarette smoke exposure nor Kras overexpression, however, significantly affected the protein levels of TNFα, p53, or cyclin D 1 in the pancreas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…dephosphorylates the G 1 cyclin, Cln2, thus maintaining its stability, while SCF Grr1 is responsible for initiating phosphorylationdependent ubiquitylation and degradation, both of which are necessary for the inactivation of G 1 cyclin-cdk activity and subsequent activation of a cyclin-cdk activity required for G 2 -M. 9 As mammalian cyclin D1 is overexpressed in human cancers, 5,48,49 and its stability is associated with defects in SCF activity, 50 targeting PP2A through inhibiting its activity may represent a plausible therapeutic for cancer treatment.…”
Section: Grr1 Is Required For the Viability Of Cdc55 Mutantsmentioning
confidence: 99%